If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 29 + -1(-1q) = 86 Remove parenthesis around (-1q) 29 + -1 * -1q = 86 Multiply -1 * -1 29 + 1q = 86 Solving 29 + 1q = 86 Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Add '-29' to each side of the equation. 29 + -29 + 1q = 86 + -29 Combine like terms: 29 + -29 = 0 0 + 1q = 86 + -29 1q = 86 + -29 Combine like terms: 86 + -29 = 57 1q = 57 Divide each side by '1'. q = 57 Simplifying q = 57
| xsquared+8x-5=15 | | g-13.37=-23 | | (0.5)(y)=3 | | 5y=175 | | 3(x-1)+60=8(x+4) | | g(-3)=2x-5 | | -30+6x=x | | -19-r=-57 | | y+17.5=49 | | -1+6x+x=-85 | | Q-65=875 | | (4+3x)(2-x)+(4-3x)(2+x)=22 | | 5x-2+4x=43 | | w+-28=-17 | | -38=-x+4x-5 | | 22x=44y | | 17y-12y=25 | | 3x-4-8x+12= | | 15-4X=-X | | 3(x-3)+5=4(x-2)-10 | | 5ab-6ab+a= | | 2senx-cosx=-4 | | P=20+6ln(2q+1) | | 13x+15=3x+215 | | B+280= | | I=IR | | 5x+5x+130=180 | | -12+5m+10m=-2m-10-m | | 4(3x+3)=14x+11-2x+1 | | (3a-5)(2a+3)=0 | | -8=x/4+3 | | 3y=5x-y |